2022
DOI: 10.3389/ijph.2022.1605074
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Roles of Dispositional Mindfulness and Cognitive Reappraisal in the Relationship Between Neuroticism and Depression Among Postgraduate Students in China

Abstract: Objectives: Previous studies revealed a positive association between neuroticism and depression. This study further extended the previous findings by exploring the psychological processes underlying this association among Chinese postgraduates. Guided by theoretical models and empirical research, we proposed a multiple mediation and moderated mediation model to investigate the roles of dispositional mindfulness and cognitive reappraisal in the relationship between neuroticism and depression.Methods: Using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
3
0
1
Order By: Relevance
“…Na última década, o número de programas de pós-graduação, em nível de mestrado e doutorado, vem crescendo de forma constante no cenário mundial e nacional e, concomitantemente, o número de discentes inseridos em tais programas. Por conseguinte, pesquisas publicadas no período de 2018 a 2023 passaram a investigar o adoecimento psíquico na vida acadêmica, evidenciando taxas variando de 15,9 a 78% de ansiedade 1,3,13,14,16,17,18,19,20,22 , 13 a 89% de depressão 1,3,13,14,16,17,18,19,20,22 , 0,99 a 31% de insônia 3,17 , 5,5% de pânico 17 e 27,4% ideação suicida passiva e 16,5% ideação suicida ativa 21 Nas amostras dos estudos analisados, cuja quantidade variou de 90 a 5.985 pósgraduandos, houve predomínio do sexo feminino e adultos jovens, com idade média de 30 anos.…”
Section: Discussionunclassified
“…Na última década, o número de programas de pós-graduação, em nível de mestrado e doutorado, vem crescendo de forma constante no cenário mundial e nacional e, concomitantemente, o número de discentes inseridos em tais programas. Por conseguinte, pesquisas publicadas no período de 2018 a 2023 passaram a investigar o adoecimento psíquico na vida acadêmica, evidenciando taxas variando de 15,9 a 78% de ansiedade 1,3,13,14,16,17,18,19,20,22 , 13 a 89% de depressão 1,3,13,14,16,17,18,19,20,22 , 0,99 a 31% de insônia 3,17 , 5,5% de pânico 17 e 27,4% ideação suicida passiva e 16,5% ideação suicida ativa 21 Nas amostras dos estudos analisados, cuja quantidade variou de 90 a 5.985 pósgraduandos, houve predomínio do sexo feminino e adultos jovens, com idade média de 30 anos.…”
Section: Discussionunclassified
“…Scores are calculated by summing the responses to the 6 relevant items, with higher scores indicating greater optimism. The LOT-R has demonstrated strong reliability and validity across different cultural contexts and has been extensively used in psychological research to measure dispositional optimism (Aldao et al, 2010;Carver & Scheier, 2014;Forgeard & Seligman, 2012;Hou et al, 2022;Lancastle, 2005;Mincu, 2015).…”
Section: Dispositional Optimismmentioning
confidence: 99%
“…Most studies have shown that mindfulness can reduce some difficulties in emotional regulation, thus promoting successful emotional regulation [18,19]. Other studies suggested that mindfulness is positively correlated with some adaptive emotion regulation strategies, such as cognitive reappraisal, while it is negatively correlated with other non-adaptive emotion regulation strategies, such as expressive suppression [20,21].…”
Section: Introductionmentioning
confidence: 99%